Comparing Behavioral and Psychological Symptoms of Dementia and Caregiver Distress Caused Between Older Adults With Dementia Living in the Community and in Nursing Homes - Lu, Xuejiao; Ye, Rui; Wu, Jialan; Rao, Dongping; Liao, Xiaoyan (Frontiers in Psychiatry, 2022)
Objectives: To investigate differences in behavioural and psychological symptoms of dementia (BPSD) and caregiver distress caused between older adults with dementia living in the community and in nursing homes. Design: A comparative cross-sectional study. Setting and Participants: Participants were recruited from outpatient clinics of a tertiary psychiatric hospital and dementia units of a nursing home in Guangzhou, China. Methods: Neuropsychiatric Inventory was used to assess symptoms and caregiver distress. Dementia severity was determined using the Clinical Dementia Rating. Results: This study included 157 community and 112 nursing home residents with dementia. Clinically significant symptoms (item score ≥ 4) were found in 88.5% of the former and 75% of the latter. Caregivers of 79.6% of the former and 26.8% of the latter reported that at least one of these caused them moderate-to-severe distress (distress score ≥ 3). Among the community patients, anxiety was the most frequent “very severe” symptom, while sleep disorders and agitation caused the most frequent “very severe” caregiver distress. After controlling for dementia severity and medication use, family caregiving remained an independent risk predictor for clinically significant symptoms and moderate-to-severe caregiver distress. The prediction of caregiver distress based on symptom scores varied across caregiver types and individual symptoms (R2 0.36–0.82). Group differences in clinically significant symptoms and moderate-to-severe caregiver distress showed at the stage of moderate-to-severe dementia. Conclusions and Implications: Tailored management strategies to relieve family caregivers’ BPSD-induced distress are needed, especially at the stage of moderate-to-severe dementia. An effective service system should be established for supporting family caregivers to cope with BPSD.